The Effect of Educational Units with Special Exercises According to the Whitley Strategy on Learning Enjoyment and Improving the Performance of the Serve and Forehand Groundstroke Skills in Tennis for Female Students - Hameed Hammad Khalaf (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
The Impact of Wheatley's Strategy on Tennis Learning and Performance Research Objectives: This study investigates the effectiveness of utilizing specialized educational units based on Wheatley’s strategy compared to traditional teaching methods. Specifically, it aims to determine how these approaches impact female students' enjoyment of learning and their proficiency in fundamental tennis skills (the serve and the forehand groundstroke), and to identify which method yields superior results. Methodology and Sample: The researcher employed an experimental methodology utilizing a pre-test and post-test design. Participants were divided into two equivalent groups: an experimental group and a control group. Target Population: The sample was deliberately selected and consisted of 33 female third-year students from the Faculty of Physical Education and Sport Sciences at the University of Anbar during the 2025/2026 academic year. Measurement and Data Analysis: To accurately evaluate the outcomes, the researcher implemented specialized tests designed to measure the students' enjoyment of learning tennis alongside their technical performance. The gathered data was then statistically processed and analyzed using the SPSS software package to verify the research hypotheses and achieve the study's objectives.